Respostas

2014-06-20T20:00:50-03:00
X + y = 3
2x - y = 0
Portanto,
x = 3 - y

2x - y = 0
2(3 - y) - y = 0
6 - 2y - y = 0
-3y = -6
y = 2

Então:
x = 3 - y
x = 3 - 2
x = 1

e

2a + b = -1
a - b = 7
Portanto,
a = 7 + b

2a + b = -1
2(7 + b) + b = -1
14 + 2b + b = -1
3b = -15
b = - 5

Então:
a = 7 + b
a = 7 - 5
a = 2

Logo,
x = 1
y = 2
a = 2
b = - 5
1 5 1
2014-06-20T20:25:31-03:00
X +y=3 (-2)           -2x - 2y = -6
2x - y= 0       >      2x - y  = 0      >   -3y= -6 (-1)  > 3y = 6  > y = 6:3  >  y = 2

2x - 2 = 0  >  2x = 2  >   x = 2:2  >  x = 1  

2a + b =-1       3a = 6  >  a = 6:3   >   a = 2           2 - b = 7   >  -b = 7 - 2
a - b =7      >                                                       -b = 5 (-1)   >  b = -5

1 1 1